Санітарно-екологічний стан гірських річок як основа екобезпеки регіону - Масікевич, Андрій Юрійович; Масікевич, Юрій Григорович (Національний університет "Львівська політехніка", 2016)
It was shown that human activities leads to destabilization of mountain ecosystems to which the natural phenomenon is the increased vulnerability and sensitivity to external changes. Over the past five years, a trend deteriorating sanitary environment quality indicators Bukovina Carpathians. Population health status Highlanders in many cases is a limiting factor for socio-economic development Bukovina Carpathians. Population health of residents of mountain regions and "health mountain ecosystems" are as interdependent and mutually the determining factors.
Keywords: екобезпека; гірські річки; гірські регіони; екосистеми; популяційне здоров'я; Буковинські Карпати